(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Extracapsular cataract extraction (ECE) is widely used in ophthalmic surgery, especially in resource-limited countries. However, despite advances in surgical technology, inflammatory complications, particularly infectious endophthalmitis, continue to pose a serious clinical problem. The purpose of this review article is to conduct a comparative analysis of the efficacy of the antibacterial drugs Levofloxacin (Levoximed) and Tobramycin in the prevention of postoperative complications in EEC. The review is based on the data of modern clinical and microbiologic studies for the last ten years. Levofloxacin was found to have a broader spectrum of action, better tissue permeability and lower flora resistance. The presented data confirm its clinical advantage as a first-line drug in antibacterial prophylaxis after ophthalmic interventions.